2019
DOI: 10.1177/1090198119853009
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Failed Grocery Store Interventions in Former Food Deserts

Abstract: Background. Implementing food stores in deprived neighborhoods to improve access to healthy food is a debated topic. Aims. To uncover important contributors to the closure of grocery store interventions in urban food deserts. Method. We systematically reviewed both peer-reviewed and gray literature for publications on the failure of grocery store interventions. Results. We found nine articles on six different failed food stores. The reasons stated for closure included low sales, a lack of food retail experienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…The scope of this case study project was broad and aimed to capture these additional elements and expand beyond healthy food access considerations, allowing us to explore in-depth strategies and shortcomings for overall store success. This expanded scope is critical, given that previous work has shown that simply opening a food store in a neighborhood with low food access does not guarantee success or improve community health outcomes [ 16 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The scope of this case study project was broad and aimed to capture these additional elements and expand beyond healthy food access considerations, allowing us to explore in-depth strategies and shortcomings for overall store success. This expanded scope is critical, given that previous work has shown that simply opening a food store in a neighborhood with low food access does not guarantee success or improve community health outcomes [ 16 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the reasons stated for their closure included poor sales, inadequate marketing, and a lack of food retail experience. This review highlighted that the reasons for store closures in this context are understudied and not reported in great detail, especially in urban settings [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Brinkley et al (2019) found community engagement critical for the long-term success of supermarket interventions in food deserts. The lack of adequate engagement of the community has been attributed to the failure of food access interventions including mobile grocery (Ramirez et al, 2017) and convenience store transformations (Engler-Stringer et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…While food insecurity is generally thought of as an economic issue in Canada ( Long et al, 2020 ), the social aspects of food insecurity as they relate to transportation infrastructure have not been explored in great depth. In Canada, populations in urban centres tend to be food insecure if they are economically disadvantaged ( Gassman-Pines and Schenck-Fontaine, 2019 ), live in food deserts ( Balcaen and Storie, 2018 , Engler-Stringer et al, 2019 ) and/or are from demographic populations more likely to experience both ( Jones et al, 2021 , Testa and Jackson, 2019 ). Food insecurity is tied to lower quality diets that ultimately lead to a variety of health and quality of life issues ( Eicher-Miller and Zhao, 2018 , Tait et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%